Frequency of severe visual disturbance associated with midfacial fractures - Faryabi J (Tehran University of Medical Sciences, 2005)
Statement of Problem: Visual loss after traumatic injuries of the maxillofacial area is one of the worst complications of these injuries and if remains untreated will affect seriously the future life of patient. Purpose: The aim of this study was to evaluate the frequency of blindness associated with midfacial fractures in Kerman Bahonar Hospital from 1996-2002. Material and Methods: This descriptive study was done retrospectively on 207 patients with midface maxillofacial trauma admitted to Kerman Bahonar Hospital from 1996 to 2002. Results: The frequency of unilateral blindness associated with midfacial trauma was 5.3 percent. The main etiologic factor was motor vehicle accidents (81.8%) and the most common area of fracture site of midface associated with blindness was Lefort III, Lefort II and NOE (Naso- Orbito- Ethmoidal) fractures. Conclusion: The evaluated frequency of blindness after midfacial injuries in this study was similar to previous studies. The etiologic factors were different from those of developed countries and similar to developing ones.